The Early Adopter Gets the Worm: Innovation Adoption of AI within a Multinational Agency - Fazrah Lillah Rizki Heryanda; Endah Murwani; Nuria Astagini (Universitas Multimedia Nusantara, 2024)
Artificial Intelligence (AI) is rapidly advancing in the advertising industry, driving multinational agencies to adopt this innovation. This study explores the adoption of AI in advertising content production, focusing on characteristics and scalability. Everett M. Rogers' Diffusion of Innovation theory serves as the conceptual framework. The research employs a descriptive qualitative approach with a case study method, collecting data through in-depth interviews with creative teams from Dentsu Indonesia, a multinational agency, and analyzing it using pattern matching. The findings reveal that Dentsu Indonesia demonstrates a proactive understanding and attitude toward AI, supported by an innovative organizational culture. The agency provides comprehensive facilities for its creative teams and implements AI in a varied and extensive manner. However, the sustainability of AI adoption faces challenges, including regulations, copyright issues, and ethics. This study offers conceptual insights into AI adoption, providing strategic perspectives for optimizing AI to enhance efficiency and productivity in the advertising industry.